Failure Mode and Effect Analysis (FMEA) Application for Safety Risk Assessment Design of “X” Bakery - Ramadhan, Rizky Fajri; Widowati, Evi; Mardiana, Mardiana (Unnes Journal of Public Health, 2019)
ABSTRACT Companies in the food sector have 8 production process lines including: receiving raw materials, storing, making dough, baking, frying, cooling, packaging, and distributing. Potential hazards can include: slipping, stuck in a mixer machine, crushed in a dough press machine, crushed in a packing machine, head hit by an elevator, short circuit, fire, explosion, leak, hot oil splash, the potential danger of ergonomics, heat stress, and respiratory disorders. This study aimed to design a risk assessment to minimize the incidence of workplace accidents. This type of research is research and development with a semi-quantitative approach. The informants were determined as many as 2 people with a purposive sampling technique. The research instrument used observation sheets, interview sheets, and FMEA worksheets. Product design is validated by an expert team. The results show 23 potential hazards in 8 production processes. The highest hazard potential is slip (RPN = 140) and the lowest is explosion (RPN = 10). So that it requires administrative control, engineering, inspection, repairs to electrical installations and gas pipes, and using personal protective equipment.   ABSTRAK Perusahaan di bidang makanan terdapat 8 alur proses produksi antara lain: Penerimaan bahan baku, penyimpanan, pembuatan adonan, pemanggangan, penggorengan, pendinginan, pengemasan, dan pendistribusian. Potensi bahaya dapat berupa: terpeleset, terjepit mesin mixer, terjepit mesin penggiling, terjepit mesin packing, kepala terbentur lift, arus pendek listrik, kebakaran, ledakan, kebocoran, percikan minyak panas,bahaya ergonomi, heat stress, dan gangguan saluran pernapasan. Penelitian ini bertujuan untuk membuat perancangan penilaian risiko untuk meminimalisir kejadian kecelakaan kerja. Jenis penelitian ini adalah research and develompent dengan pendekatan semi kuantitatif. Informan yang ditetapkan sebanyak 2 orang dengan teknik purposive sampling. Instrumen penelitian menggunakan lembar observasi, lembar wawancara, dan FMEA worksheet. Desain produk dilakukan validasi oleh tim pakar. Hasil menunjukkan  23 potensi bahaya tersebar di 8 proses produksi. Potensi bahaya tertinggi adalah terpeleset (RPN=140) dan terendah adalah ledakan (RPN=10). Sehingga diperlukan pengendalian administratif, rekayasa teknik, inspeksi secara ruitn, perbaikan terhadap instalasi listrik dan pipa gas, serta menggunakan alat pelindung diri. Kata Kunci     : Failure Mode and Effect Analysis (FMEA), Potensi Bahaya, Penilaian Risiko.